In vivo precision of conventional and digital methods for obtaining quadrant dental impressions - Ender, Andreas; Zimmermann, Moritz; Attin, Thomas; Mehl, Albert (Clinical oral investigations, 2016)
Objectives Quadrant impressions are commonly used as alternative to full-arch impressions. Digital impression systems provide the ability to take these impressions very quickly; however, few studies have investigated the accuracy of the technique in vivo. The aim of this study is to assess the precision of digital quadrant impressions in vivo in comparison to conventional impression techniques. Materials and methods Impressions were obtained via two conventional (metal full-arch tray, CI, and triple tray, T-Tray) and seven digital impression systems (Lava True Definition Scanner, T-Def; Lava Chairside Oral Scanner, COS; Cadent iTero, ITE; 3Shape Trios, TRI; 3Shape Trios Color, TRC; CEREC Bluecam, Software 4.0, BC4.0; CEREC Bluecam, Software 4.2, BC4.2; and CEREC Omnicam, OC). Impressions were taken three times for each of five subjects ( n = 15). The impressions were then superimposed within the test groups. Differences from model surfaces were measured using a normal surface distance method. Precision was calculated using the Perc90_10 value. The values for all test groups were statistically compared. Results The precision ranged from 18.8 (CI) to 58.5 μm (T-Tray), with the highest precision in the CI, T-Def, BC4.0, TRC, and TRI groups. The deviation pattern varied distinctly depending on the impression method. Impression systems with single-shot capture exhibited greater deviations at the tooth surface whereas high-frame rate impression systems differed more in gingival areas. Triple tray impressions displayed higher local deviation at the occlusal contact areas of upper and lower jaw. Conclusions Digital quadrant impression methods achieve a level of precision, comparable to conventional impression techniques. However, there are significant differences in terms of absolute values and deviation pattern. Clinical relevance With all tested digital impression systems, time efficient capturing of quadrant impressions is possible. The clinical precision of digital quadrant impression models is sufficient to cover a broad variety of restorative indications. Yet the precision differs significantly between the digital impression systems.